EXTERNAL ASSESSMENTS AND EDUCATIONAL INEQUALITIES: WHAT THE SAEB RESULTS REVEAL - da Silva , Clebercy Araújo; Ferreira , Claudia Rosana Speiss; Naziazeno , Dalva da Silva Gomes; Santos , Érica Maiara Araújo; Santos , Joseane de Souza; Mancuso, Leandra Rafaella França; Pinto , Luzeni dos Santos; dos Anjos , Maiza Vieira; Almeida, Marta Regina; Dias, Sara de Oliveira; Drisner, Thales Horst; da Silva, Valdeci Castro; et al. (Editora Impacto Científico, 2025)
This study seeks to explore the revelations about educational inequalities in Brazil based on the results of the Basic Education Assessment System (SAEB), highlighting the importance of external assessments in the educational context. We analyze how such assessments reveal disparities in access to and quality of education, contributing to the debate on equity in education. The research is based on theories from renowned authors in the field of education, such as Dermeval Saviani, José Carlos Libâneo, Pedro Demo, and Cipriano Luckesi, as well as specialists in educational assessment such as Luiz Carlos de Freitas, Tereza Helena Olinda Bonamino, and José Francisco Soares. We reflect on the role of accountability policies in perpetuating educational inequalities and discuss the limitations of SAEB as an assessment instrument. The conclusions point to the need for reformulations in public education policies, aiming at equity and effective inclusion, as well as a critical review of the methodologies used for the analysis and interpretation of data from SAEB.DOI: https://doi.org/10.56238/edimpacto2025.092-038